Rehabilitation after anteromedialization of the tibial tuberosity - Salari, N.; Horsmon, G. A.; Cosgarea, A. J. (Clinics in Sports Medicine, 2010)
Various surgical procedures are currently being used to treat symptomatic patellar instability. Distal bony realignment techniques attempt to correct malalignment by shifting the site of insertion of the patellar tendon. Tibial tuberosity anteromedialization, also known as the Fulkerson osteotomy, is a process in which the tuberosity is transferred anteriorly and medially. Although this surgical technique has been well described in the literature and the results are generally reported to be very good, the operation requires a prolonged recovery period and little has been written specifically regarding postoperative rehabilitation. This article discusses the rationale and technique for anteromedialization and emphasizes the important principals and goals of rehabilitation.